The importance of oracle rejoining in the study of ancient characters and the history of the Shang Dynasty. (March 2019) - Zhang, Weijie
Abstract: From the beginning of the unearthing of oracle bones in Anyang Henan, traditional descriptions of the ancient history of China have been gradually modified. It is regrettable that the disaster of non-scientific excavations and long-distance transit happened at almost the same time. From knowing the history of the damage to the oracle bones, we can then understand how important the recovery work is. The rejoining work began early in the 20th century, and many scholars have contributed to the related work. The seven examples in this article present multiple values regarding not only recovering the broken oracle bones to their original state, but also 'highlighting the particular phenomenon of culture', 'getting the real recovery of inscriptions', and 'verifying the authenticity of documents'. This speaks well of the important rejoining work which benefits the study of ancient characters and Yin Shang history. After all, to use the oracles as a tool to study ancient characters and history, we should first undertake rejoining and restore them to their original appearance.